Relevance and prospect of development of imitating modelling at research of working process of the excavator - A. I. Demidenko; A. B. Letopolsky; D. S. Semkin (Вестник СибАДИ)
A scraper design with rotary loading. Substantiates the location of the rotor blades to provide a bucket load and complete unloading. The question of filling the bucket scraper height and location of the rotor shaft to operate the scraper without pusher. Presented calculated according to the definition of the scraper bucket capacity with the rotor load, the radius of the rotor circumference and the height of the side walls of the bucket. The recommendations of the angle of inclination of the rear wall of the bucket to the vertical and location podnozhevoy plate.